Soil respiration and the environment - Luo, Yiqi (Academic Press, 2006)
This book synthesizes the already published research findings and presents the fundamentals of this subject. Including information on global carbon cycling, climate changes, ecosystem productivity, crop production, and soil fertility, this book will be of interest to scientists, researchers, and students across many disciplines